Exploring Factors of Preschool Parents’ Behavioral Intention to Use Face Recognition Technology on Campus - Liu, Yinsheng; Zhao, Li; Su, Yu-Sheng (Frontiers in Physics, 2022)
Face recognition technology (FRT) is being increasingly used to record the trajectory of human behavior due to its non-contact nature and high accuracy. When the technology is extended to education, it is applied to manage students’ access to campus, to analyze learning behaviors, and to monitor students’ campus activities. It is important to note that the use of face recognition technology for students on campus should be approved by the students’ guardians. Therefore, this study aimed to determine what factors affect the behavioral intentions of preschool parents’ adoption of facial recognition systems on campus. Unlike previous studies, the model of this study was designed to focus not only on the affective dimension, but also on the parenting style. The model was validated with data from an online questionnaire completed by 419 preschool parents. AMOS was used to analyze various assumptions of the model. The analysis revealed that innate consumer innovativeness positively influenced experience values and helicopter parenting which directly affected their behavioral intentions. The results imply that in the application of face recognition technology, parents’ behavioral intentions depend not only on the prior experiential value of the product and helicopter parenting, but also on parents’ innate consumer innovativeness. Therefore, for campus management and technology application, this study is useful to understand the behavioral intention of guardians to use the new technology. For operators and users of face recognition technology, this study provides several guidelines for exploring parental attitudes toward child supervision and improving products and services to value information security.